International diversification after 1985: The argument becomes stronger - G. D.I. Barr (South African Journal of Business Management, 1986)
The performance of South African traded securities vis-à-vis securities on two overseas stock exchanges is considered in this article. It can be seen how the recent political instability in South Africa and the associated depreciation in the rand have led to dramatic returns, in rand terms, on those overseas markets. It is argued that these large returns on foreign markets may well not be repeated but that the increased risk of South African assets has made the diversification benefit of overseas investment that much greater. It therefore appears that serious consideration should be given to allowing certain institutions to have some holding of foreign assets so as to offer some protection to the real value of South African savings.
Keywords: 650